The deserving : what the lives of the condemned reveal about American justice - Vartkessian, Elizabeth S. (Elizabeth Stanislawa), 1981- (Bloomsbury Publishing, 2026)
"Elizabeth Vartkessian works with criminal defense teams as a mitigation specialist. She isn't part of the Innocence Project; her clients are often legally guilty, and often of terrible crimes. Rather,her job is to spend hundreds of hours per case talking to the parents, siblings, teachers, and neighbors of a defendant, situating their crimes in context. Founder and director of nonprofit mitigation team Advancing Real Change Inc., Vartkessian weaves powerful, grippingstories from her ... career into an inspiring argument for dignity in American justice. Her unique experience has taught her that whenpersonal or generational trauma enters the body, it finds its way out eventually, sometimes through violence. She contends that we cannot hold her clients solely responsible for their actions, nor can we continue to stomach harsh penalties that deny real justice to perpetrators and victims alike"--